Prevajanje danes in jutri - Hirci, Nataša (Jezik in slovstvo, 2003)
The present paper discusses various contemporary translation tools and resources in the electronic form available to translators. The overview of the different types of language technologies and electronic resources is corroborated with practical examples of applying such translation tools for the Slovene language to translation. At the time of globalisation and European integration processes important to Slovenia, these tools facilitate a faster and more effective translation of certain text types; thus, translators, aiming to remain competitive in the increasingly demanding translation market, need to be both familiar with IT and skilled in the implementation of contemporary translation tools.
Keywords: Slovene; slovenščina; translation; prevajanje; jezikovne tehnologije; Language technology; korpusno jezikoslovje; Corpus linguistics; computational linguistics; računalniško jezikoslovje